Peramalan Harga Gabah Kering Panen Menggunakan Metode Seasonal Autoregressive Integrated Moving Average (SARIMA) Di Kabupaten Banyuwangi - Akmalia Zumarotul Karomah; Riza Rahimi Bachtiar; Nur Syamsi Aisyah; Aldy Bahaduri Indraloka (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2026)
Harvested Dry Paddy is a strategic agricultural commodity that plays an important role in increasing farmers' income and maintaining food security in Banyuwangi Regency. Fluctuations in Harvested Dry Paddy prices, influenced by changes in production, harvest seasons, and market conditions, require appropriate forecasting to support decision-making. This study aimed to analyze price trends, identify seasonal patterns, and forecast Harvested Dry Paddy prices in 2026 using the Seasonal Autoregressive Integrated Moving Average (SARIMA) method. A descriptive quantitative approach was employed using monthly Harvested Dry Paddy price data from 2020 to 2025 obtained from Statistics Indonesia (BPS) of Banyuwangi Regency. The analysis followed the Box–Jenkins procedure, including stationarity testing, model identification, parameter estimation, diagnostic checking, model selection, and forecasting. The results showed that Harvested Dry Paddy prices fluctuated during the observation period with an increasing trend and exhibited a seasonal pattern at lag 12. The initial data were non-stationary, as indicated by an Augmented Dickey-Fuller (ADF) probability value of 0.1311; therefore, differencing was performed until stationarity was achieved. The best forecasting model was SARIMA (2,1,1)(0,1,1)12. The forecasting results indicated that Harvested Dry Paddy prices in 2026 are expected to range from IDR 7,137.47/kg to IDR 9,209.91/kg, with a gradual upward trend despite continuing fluctuations.